PEWARISAN GEN PENANDA HPT(HYGROMYCINE PHOSPHOTRANSFERASE) BERDASARKAN ANALISIS PCR DAN EKSPRESINYA PADA POPULASI PADI TRANSFORMAN MENGOVEREKSPRESIKAN GEN HD ZIP OSHOX-6 - Enung Sri Mulyaningsih; Hajrial Aswidinnoor; Didy Sopandie; Pieter BF OuwerkerV; Inez Hortense Slamet Loedin (BERITA BIOLOGI, 2010)
First generation (TO) transgenic plants do not always segregate their transgenes in a Mendellian segregation pattern. Moreover,instability of heterologous gene expression was often observed in transgenic plants. This phenomenon is often called gene silencing. Gene silencing could happen on different level of gene expression, notably at transcriptional or post-transcriptional level.The purpose of this research was to identify the transgene segregation pattern of a marker gene (hpt) as well as the introduced- regulator gene (OsLEA-oshox6) in second generation (Tl) transgenic rice plants.Gene segregation (hpt) analysis was carried out using PCR method. Gene expression analysis was done by hygromycin antibiotic resistant test of leaf samples.Analysis was carried out on 17 lines of Tl transgenic rice plants from Batutegi and Kasalath cultivars.Mendellian segregation pattern of 3:1 was revealed for all lines based on PCR analysis. Gene expression analysis showed almost all lines was segregated in a Mendellian fashion except for Tl-BT III 2C line. Less transgenic plants that expressed the hpt gene were suggested due to gene silencing effects.It was suggested to happen at transcriptional level.